2018
DOI: 10.21608/ejhm.2018.12382
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Diet Therapy in the Management and Prevention of Acne Vulgaris

Abstract: Background: Acne is a widespread and complex skin disease among developed nations, affecting nearly all young adults between the ages of 15 to 17 years. It is a chronic inflammatory skin disorder resulting in psychological stress. Historically, the relationship between diet and acne is controversial. As a result, significant studies have been done to evaluate this relationship. Assessment of these literatures will help to provide better outcomes for the patients.Objective:This study aims to: 1-Measuring effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Moreover, as opposite to the previous diet, the western diet and especially fast food have been studied and they showed that these have an aggravating effect on acne. This was attributed mainly to industrially produced trans fatty acids and saturated fats that compose the main bulk of these dietary options (48). Most of our patients which were not eat fish as shown in table 3.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, as opposite to the previous diet, the western diet and especially fast food have been studied and they showed that these have an aggravating effect on acne. This was attributed mainly to industrially produced trans fatty acids and saturated fats that compose the main bulk of these dietary options (48). Most of our patients which were not eat fish as shown in table 3.…”
Section: Resultsmentioning
confidence: 87%